2023
DOI: 10.1001/jamanetworkopen.2023.21939
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Accessibility Under the State Standing Order Across Mississippi

Abstract: ImportanceNaloxone is a life-saving medication for individuals experiencing an opioid overdose. Naloxone standing orders aim to make naloxone more available by allowing patients improved access to this medication at community pharmacies; however, lawful availability does not mean that this life-saving intervention is accessible to patients.ObjectiveTo characterize naloxone availability and out-of-pocket cost under the state standing order in Mississippi.Design, Setting, and ParticipantsThis telephone-based, my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Despite policies to increase naloxone access at pharmacies, its availability has remained suboptimal . Secret shopper studies, studies in which individuals pose as patients to evaluate access to care, found that same-day access to naloxone varied from as low as 23.5% of pharmacies in California to as high as 96.1% of pharmacies in Massachusetts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite policies to increase naloxone access at pharmacies, its availability has remained suboptimal . Secret shopper studies, studies in which individuals pose as patients to evaluate access to care, found that same-day access to naloxone varied from as low as 23.5% of pharmacies in California to as high as 96.1% of pharmacies in Massachusetts .…”
Section: Introductionmentioning
confidence: 99%
“…Despite policies to increase naloxone access at pharmacies, its availability has remained suboptimal. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Secret shopper studies, studies in which individuals pose as patients to evaluate access to care, found that same-day access to naloxone varied from as low as 23.5% of pharmacies in California to as high as 96.1% of pharmacies in Massachusetts. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 When comparing naloxone access by pharmacy type, independent pharmacies, or pharmacies that follow the small owner/operator model, have lower naloxone availability compared with chain pharmacies, or pharmacies that are part of a corporation or have more than 5 locations.…”
Section: Introductionmentioning
confidence: 99%